28th International Symposium on Automation and Robotics in Construction (ISARC 2011) 2011
DOI: 10.22260/isarc2011/0004
|View full text |Cite
|
Sign up to set email alerts
|

Visual Req Calculation Tool for Green Building Evaluation in Taiwan

Abstract: ABSTRACT:The concept of a "green building" was first introduced to Taiwan in 1999, and began to develop regulations for the design and evaluation of energy-saving buildings. The Ratio of Equivalent Transparency (Req) is a basic index for assessing whether a building is energy-efficient. Req is the ratio of the area of total building envelope and the area of envelope equivalent transparency. Calculation of Req requires not simply the consideration of natural factors such as building location, direction, ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Krygiel and Nies [64] summarised the different ways that BIM can aid in planning and design for building sustainability. The benefits they identified included the following: i) assessing the building's orientation (for selecting a good orientation that can reduce energy costs); ii) analysing the building's massing (for analysing building's form and optimising the building's envelope in terms of various factors such as the ratio of equivalent transparency (Req) (see [29]); iii) conducting daylighting analysis; iv) investigating the water harvesting potential (for reducing water requirements in a building); v) modelling building energy performance (for reducing energy needs or analysing renewable energy options that can contribute to low energy costs (see [58]); vi) examining the suitability of sustainable materials (for reducing material needs and using recycled materials) and vii) designing site and logistics management (for minimising wastes and carbon footprints). Clevenger and Khan [125] evaluated the contribution of BIM to the design-to-fabrication process for building materials.…”
Section: Building Planning and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Krygiel and Nies [64] summarised the different ways that BIM can aid in planning and design for building sustainability. The benefits they identified included the following: i) assessing the building's orientation (for selecting a good orientation that can reduce energy costs); ii) analysing the building's massing (for analysing building's form and optimising the building's envelope in terms of various factors such as the ratio of equivalent transparency (Req) (see [29]); iii) conducting daylighting analysis; iv) investigating the water harvesting potential (for reducing water requirements in a building); v) modelling building energy performance (for reducing energy needs or analysing renewable energy options that can contribute to low energy costs (see [58]); vi) examining the suitability of sustainable materials (for reducing material needs and using recycled materials) and vii) designing site and logistics management (for minimising wastes and carbon footprints). Clevenger and Khan [125] evaluated the contribution of BIM to the design-to-fabrication process for building materials.…”
Section: Building Planning and Designmentioning
confidence: 99%
“…However, without detailed prediction and planning for the types and volumes of recycled building materials, it can be time-consuming and expensive for contractors and recyclers to conduct a material recycling process [32]. If a building is • Wu and Issa [110] • Zhai and McNeill [117] • Hammond et al [50] • Frank et al [43] • • Jalaei and Jrade [55] • Wu et al [111] • Zuo and Zhao [118] • Wong and Kuan [104] • Inyim et al [54] • Volk et al [101] • • • Lin and Gerber [71] • Katranuschkov et al [58] • Kandil et al [119] • Gandhi and Jupp [44] • Russell-Smith and Lepech [90] • • • • • Wong et al [106] • Eadie et al [40] • Costa et al [36] • Cooley and Cholakis [120] • Costin et al [37] • Clevenger and Khan [34] • Cheng and Ma [32] • Chi et al [33] • • • Wong and Lau [105] • Yeheyis et al [113] • • Wong and Fan [107] • Buyle et al [27] • König et al [61] • Jrade and Jalaei [57] • Motawa and Almarshad [79] • Motawa and Carter [80] • • • • • • Liao et al [70] • Wu and Issa [108] • Rajendran et al [89] • Rajendran and Gomez [88] • • Cheng and Ma [31] • Jiang et al [56] • Bynum et al [28] • • Azhar et al [15] • Chang et al …”
Section: Building Demolitionmentioning
confidence: 99%
“…Wong and Zhou [17] reviewed the previous green BIM research over building lifecycles and defined green BIM as "a model based process of generating and managing coordinated and consistent building data during its project lifecycle that enhance building energy efficiency performance, and facilitate the accomplishment of established sustainability goals". Lu et al [5] concluded that the majority of green BIM applications were designed for building performance analysis and simulations, such as energy performance analysis [18][19][20][21][22][23][24], embodied carbon dioxide emission analysis, lighting simulations and some integrated building performance optimization [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%